Prostate carcinoma cell-derived exosomal MicroRNA-26a modulates the metastasis and tumor growth of prostate carcinoma - Wang, Xiaobin; Wang, Xi; Zhu, Zhiyi; Li, Wensheng; Yu, Guoqiang; Jia, Zhaohui; Wang, Xiangwei (Biomedicine & pharmacotherapy, 2019)
Prostate carcinoma may develop into metastatic castration-resistant prostate carcinoma (mCRPC) after endocrine therapy. Exosomal microRNAs play an important role in the regulation of tumor microenvironment. Our study aimed to investigate the effect of exosomal miR-26a on tumor phenotype of prostate carcinoma. Low-grade prostate carcinoma cell line (LNCAP) and mCRPC cell line (PC-3) were treated as experimental subjects according to their miR-26a expressions. Wound healing, transwell and colony-forming unit assays were performed after miR-26a mimic/inhibitor transfection. Then, exosomes were isolated from LNCAP and PC-3 cells, and the levels of exosomal miR-26a were determined. After co-culture of LNCAP (PC-3) cells with PC-3 (LNCAP) exosomes, changes in malignant behaviors were measured. Moreover, LNCAP/PC-3 exosomes were injected into xenograft tumor mice to determine effects of the exosomes on tumorigenicity of LNCAP and PC-3 cells. MiR-26a showed a potently inhibitory effect on cell proliferation, migration and invasion of LNCAP and PC-3 cells. LNCAP exosomes had a higher miR-26a level, compared with PC-3 exosomes. Overexpression of miR-26a attenuated the enhanced malignant behavior of LNCAP cells induced by PC-3 exosomes, and miR-26a inhibition could reverse the inhibitory effects of LNCAP exosomes on PC-3 cells. Exosomal miR-26a could significantly alter the expressions of epithelial-mesenchymal transition (EMT)-related factors. Moreover, LNCAP exosomes suppressed the tumorigenicity of PC-3 cells, while PC-3 exosomes could promote the tumorigenicity of LNCAP cells. Our data suggest that exosomal miR-26a derived from prostate carcinoma cells had a suppressive effect on the metastasis and tumor growth of prostate carcinoma.